The political economy of green growth: Illustrations from Southern Africa - Danielle Resnick; Finn Tarp; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The concept of green growth implies that a wide range of developmental objectives, such as job creation, economic prosperity and poverty alleviation, can be easily reconciled with environmental sustainability. This study, however, argues that rather than being win-win, green growth is similar to most types of policy reforms that advocate the acceptance of short-term adjustment costs in the expectation of long-term gains. In particular, green growth policies often encourage developing countries to redesign their national strategies in ways that might be inconsistent with natural comparative advantages and past investments. In turn, there are often sizeable anti-reform coalitions whose interests may conflict with a green growth agenda. We illustrate this argument using case studies of Malawi, Mozambique, and South Africa, which are engaged in development strategies that involve inorganic fertilizers, biofuels production, and coal-based energy, respectively. Each of these countries is pursuing an environmentally suboptimal strategy but nonetheless addressing critical development needs, including food security, fuel, and electricity. We show that adopting a green growth approach would not only be economically costly but also generate substantial domestic resistance, especially amongst the poor.
Keywords: D72; N57; P48; Q00; 330; development policy; green growth; political economy; Southern Africa; Wirtschaftswachstum; Nachhaltige Entwicklung; Entwicklungspolitik; Wirtschaftswissenschaft; Südliches Afrika